Pengaruh Pengungkapan Corporate Social Responsibility Dan Kinerja Lingkungan Terhadap Return On Asset - Nur Afifah Insani; Syamsul Huda (Universitas Bandar Lampung (UBL), 2026)
This study aims to analyze and test both partially and simultaneously the effect of corporate social responsibility disclosure and environmental performance on return on assets in companies within the metals and minerals subsectors listed on the Indonesia Stock Exchange from 2020 to 2023. The population in this study consists of 35 companies in the metals and minerals subsectors listed on the Indonesia Stock Exchange during the 2020 to 2023 period. The sampling technique used is purposive sampling . Data analysis methods include descriptive and verificative analysis, with hypothesis testing conducted using multiple linear regression with SPPS Version 26. The results indicate that (1) corporate social responsibility disclosure partially affects return on assets, (2) environmental performance partially does not affect return on assets, and (3) corporate social responsibility disclosure and environmental performance simultaneously affect return on assets.